2012
DOI: 10.1007/s10863-012-9424-5
|View full text |Cite
|
Sign up to set email alerts
|

ATAD3, a vital membrane bound mitochondrial ATPase involved in tumor progression

Abstract: ATAD3 (ATPase family AAA Domain-containing protein 3) is a mitochondrial membrane bound ATPase whose function has not yet been discovered but its role is essential for embryonic development. The ATAD3 gene has existed since the pluri-cellular organisms with specialized tissues and has remained unique until vertebrates. In primates and human, two other genes have appeared (called ATAD3B and ATAD3C versus ATAD3A the ancestral gene). ATAD3 knock-down in different non-transformed cell lines is associated with dras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…ATAD3A belongs to ATPase family of mitochondrial membrane proteins which is involved in mitochondrial fragmentation, cellular autophagy and ER-mitochondrial communication282937. In this study, results demonstrated that ATAD3A expression was closely associated with BmNPV infection similar with a previously reported study on HPV infection (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ATAD3A belongs to ATPase family of mitochondrial membrane proteins which is involved in mitochondrial fragmentation, cellular autophagy and ER-mitochondrial communication282937. In this study, results demonstrated that ATAD3A expression was closely associated with BmNPV infection similar with a previously reported study on HPV infection (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…S2A and S2B)2829. HSPD1 contains a highly conserved Cpn-TCP160 functional domain and plays an essential role in protein folding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These features are known to correlate with high mutation rates, suggesting mutations in these genes may be mechanistically favored rather than selected (42). ATAD3B encodes a mitochondrial ATPase essential for embryonic development, which has been implicated in control of proliferation in cancer cell line models (43). The CNS-specific transcription factor BHLHE22 contributes to cell fate determination and proliferation, although its role in oncogenesis remains to be established (44, 45).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this importance of mitochondrial CL trafficking, the molecular mechanisms involved and their regulation are poorly defined. Few proteins were reported or suspected so far to exchange lipids between mitochondrial membranes, including tBid (26), ATAD3 (27,28), and Ups1 (29,30), and to promote the necessary lipid flip-flop between inner and outer membrane leaflets, including proteins like scramblase 3 (31,32) or Bax (33).…”
mentioning
confidence: 99%